Retinal response to systemic inflammation differs between sexes and neurons - Rodríguez-Ramírez, Kristy T.; Norte-Muñoz, María; Lucas-Ruiz, Fernando; Gallego-Ortega, Alejandro; Calzaferri, Francesco; García-Bernal, David; Martínez, Carlos M.; Galindo-Romero, Caridad; de los Ríos, Cristóbal; Vidal-Sanz, Manuel; Agudo-Barriuso, Marta (Frontiers in Immunology, 2024)
Background Neurological dysfunction and glial activation are common in severe infections such as sepsis. There is a sexual dimorphism in the response to systemic inflammation in both patients and animal models, but there are few comparative studies. Here, we investigate the effect of systemic inflammation induced by intraperitoneal administration of lipopolysaccharide (LPS) on the retina of male and female mice and determine whether antagonism of the NLRP3 inflammasome and the extrinsic pathway of apoptosis have protective effects on the retina. Methods A single intraperitoneal injection of LPS (5 mg/kg) was administered to two months old C57BL/6J male and female mice. Retinas were examined longitudinally in vivo using electroretinography and spectral domain optical coherence tomography. Retinal ganglion cell (RGC) survival and microglial activation were analysed in flat-mounts. Retinal extracts were used for flow cytometric analysis of CD45 and CD11b positive cells. Matched plasma and retinal levels of proinflammatory cytokines were measured by ELISA. Retinal function and RGC survival were assessed in animals treated with P2X7R and TNFR1 antagonists alone or in combination. Results In LPS-treated animals of both sexes, there was transient retinal dysfunction, loss of vision-forming but not non-vision forming RGCs, retinal swelling, microglial activation, cell infiltration, and increases in TNF and IL-1β. Compared to females, males showed higher vision-forming RGC death, slower functional recovery, and overexpression of lymphotoxin alpha in their retinas. P2X7R and TNFR1 antagonism, alone or in combination, rescued vision-forming RGCs. P2X7R antagonism also rescued retinal function. Response to treatment was better in females than in males. Conclusions Systemic LPS has neuronal and sex-specific adverse effects in the mouse retina, which are counteracted by targeting the NLRP3 inflammasome and the extrinsic pathway of apoptosis. Our results highlight the need to analyse males and females in preclinical studies of inflammatory diseases affecting the central nervous system